Viabilidade econômica do processo de obtenção de biomassa pigmentante de Rubrivivax gelatinosus - Lima, Leandro kanamaru Franco de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
effluent to assess studies on cell mass production, yield, productivity, Chemical Oxygen Demand (COD) and economic viability of a project to produce bacterial biomass on an industrial scale. Initially, different concentrations of the substrate were performed with the purpose of increasing the productivity and the biomass recovery (¼, ½ and ¾ the initial volume) using microfiltration. Cultivations was accomplished in bioreactors (50 L), at 1,500 ± 200 lux, 32 ± 2°C during 5 days. The biomass was recovery by microfiltration then freeze-dried. Later, the biomass samples were analyzed regarding to proximate composition. Thus, an analysis was developed to assess the resources necessary to estimate costs and revenue that might occur during the project operating (10 years). The main viability indicators used were the Net Present Value (NPV), the Internal Rate of Return (IRR) and the payback. The results showed greater recovery and biomass productivity in bioreactor with higher organic matter (28.61 ± 0.71 g and 0.1144 g biomass L-1 day-1). The greater COD reduction was 69.23%. Except for the lipids and proteins, whose concentrations were higher in the biomass produced in the most concentrated substrates, the other components remained the same. Regarding the economic viability, the results showed that, with a productivity of 0.085 g biomass L-1 day-1, 9.58 tons of biomass could be produced during one year. The total investment for the project was estimated in R$ 6,361,456.51, with an annual costs of R$ 2,366,131.38 and incomes of R$ 3,870,913.15. Considering these results and the viability indicators of 23.70% for the IRR and R$ 4,466,192.26 for the NPV, per annum, the project was considered feasible, providing the recovery of the invested capital within 3.98 years of activity.
Keywords: Biomassa; Carotenoides; Bactérias; Economia; Efluente - Qualidade; Biotecnologia; Fishing industry efflents